Tool Wear Measurement Using Machine Vision. - Ratnam, Mani Maran (Universiti Sains Malaysia, 2008)

(untitled)
Tool wear has been extensively studied in the past due to its effect on the surface quality of the finished product.Vision-based systems using a CCD camera are increasingly being used for measurement of tool wear due to their numerous advantages compared to indirect methods.